Spanish Translation for Astronomy Outreach - Lattis, James M. (Proceedings of the Wisconsin Space Conference, 2011)
Astronomy and space science outreach to the Hispanic community in Madison has taken many forms and presents many challenges. With support from WSGC, UW Space Place has experimented with a wide variety of Spanish-language outreach, including both bi-lingual (English presentation with simultaneous translation into Spanish) and Spanish-only interactive sessions, lectures in Spanish, star parties with Spanish interpreters present, community science â€œfairsâ€ targeted for the Spanish-speaking community, and Spanish translations of exhibit materials. (See proceedings paper from last year.) In addition to the program development itself, each of these types of outreach requires Spanish-language promotional materials, support materials (e.g. agendas and event maps), and supplementary materials, such as take-home brochures. Thus, the simple-sounding process of translation itself arises constantly, although in different contexts, from beginning to end. I report here on the particular matter of translating outreach material of various sorts into Spanish. The appendix to this report contains examples of this translation work, funded entirely by WSGC.Â